The Dual Role of HLA-G in Cancer - Nathalie Rouas-Freiss; Philippe Moreau; Joel LeMaoult; Edgardo D. Carosella (Journal of Immunology Research)
We here review the current data on the role of HLA-G in cancer based on recent findings of an unexpected antitumor activity of HLA-G in hematological malignancies. For the past decade, HLA-G has been described as a tumor-escape mechanism favoring cancer progression, and blocking strategies have been proposed to counteract it. Aside from these numerous studies on solid tumors, recent data showed that HLA-G inhibits the proliferation of malignant B cells due to the interaction between HLA-G and its receptor ILT2, which mediates negative signaling on B cell proliferation. These results led to the conjecture that, according to the malignant cell type, HLA-G should be blocked or conversely induced to counteract tumor progression. In this context, we will here present (i) the dual role of HLA-G in solid and liquid tumors with special emphasis on (ii) the HLA-G active structures and their related ILT2 and ILT4 receptors and (iii) the current knowledge on regulatory mechanisms of HLA-G expression in tumors.